Computational Insights Into the Inhibition Mechanism of Proanthocyanidin B2 on Tau Hexapeptide (PHF6) Oligomer - Li, Qin; Xiong, Chunmei; Liu, Hongli; Ge, Huizhen; Yao, Xiaojun; Liu, Huanxiang (Frontiers in Chemistry, 2021)
The formation of amyloid fibrils from Tau is a key pathogenic feature of Alzheimer’s disease (AD) and to disturb the formation of Tau aggregate is considered as a promising therapeutic strategy for AD. Recently, a natural product proanthocyanidin B2 (PB2) was confirmed to not only inhibit the amyloid formation of Tau, but also disaggregate its preformed amyloid fibrils. Here, to explore the inhibition mechanism of PB2 against Tau fibril and provide the useful information for the discovery of inhibitors, all-atom molecular dynamics simulations were performed for the ordered Tau hexapeptide PHF6 oligomer in the presence and absence of PB2. The obtained result shows that PB2 can transform PHF6 oligomer from the ordered β-sheet structure into disordered one. Moreover, the clustering analysis and binding free energy calculations identify that S3 site is the most possible binding site. In S3 site, the residues V309, Y310 and K311 play a key role in the binding with PB2 by hydrophobic and hydrogen bond interactions, especially K311. In a word, our results uncover the molecular mechanism of PB2 inhibiting PHF6 aggregation and it will provide valuable information for the development of new drugs to inhibit Tau aggregation.